Computer Simulation Integration in Secondary Physics: Understanding its Nature, Impacts, and Challenges - Jovalson Abiasen; Gaudelia Reyes (International Journal of Asian Education, 2021)
This paper explored the teaching experiences of physics teachers in integrating computer simulations in their pedagogy to promote a constructivist learning environment. Its objectives are to determine how physics teachers describe computer simulations based on how they are used, how these are embedded in the teaching-learning process, their impact on the teaching-learning process, and the challenges of integrating these into physics teaching. Using the phenomenological design, two themes emerged for the first objectives, which are process-based and system-based. First, the teacher-manipulated with sub-themes of engaging, demonstrating, elaborating, and evaluating, and student-manipulated emerged on how the simulations are used. Second, the impact to teaching generated knowledge-based, skill-based, and value-based learning-based primarily on the three learning domains. Also, respondents emphasized that the integrations of computer simulations are convenience, efficacy, and heterogeneity. Finally, the challenges in the integration process are classified as teacher and school-related.  The results showed that teachers are integrating computer simulations differently depending on their resources and the TPACK knowledge.